Cobertura vacinal em queda: a saúde coletiva em risco de doenças virais reemergentes no Brasil - Viana, Rafaela Rodrigues (2024)
A drastic reduction in vaccination coverage in recent years has resulted in the return of vaccine- preventable diseases. Some justifications include: mistaken perception on the part of the population that the diseases have disappeared and failure to record information in a computerized manner. The main objective of this study is to analyze the vaccination coverage of vaccines for viral diseases that make up the basic calendar for children under 5 years of age. This is an ecological study of temporal and geospatial trends, descriptive and analytical of the vaccination coverage of viral immunizations in children under 5 years of age in Brazil and Ceará, between the years 1994 and 2022. The data come from the National Immunization Plan. Analytical trend graphs were created using the JoinPoint Regress Program software (Version 5.0.2). To create vaccination maps for Brazil and the state of Ceará, the QGIS software (Version 2.18) was used. The study data reflects a sharp drop in the vaccination coverage indicator in the country during the period studied. Vaccination coverage was lower during 2021, equivalent to 60.68%. In the temporal trend analysis in the country, an active drop in the majority of vaccines was found, with statistical significance. Ceará followed the same line as the rest of the country, with similar APC, IC and p-value indices for most immunizers, identifying the oscillation in different states from 2014 onwards. It was identified that vaccination coverage rates are distributed homogeneously between Brazil and the state of Ceará. Geostatistics methods made it possible to quantify and identify the aggregates with the lowest rates of the indicator in the states, Acre and Roraima respectively. In Ceará, the lowest vaccination coverage rates in 2014 and 2022 were Irauçuba and Maracanaú, being areas of greater severity for the indicator. Vaccination coverage of viral immunizers was much lower in the groups identified in the study, with no prospect of the WHO target being achieved by the end of 2025. Therefore, it is necessary to intensify actions and invest in education of the population and professionals to mitigate efforts to recover the indicator rates in all regions of the country.